Insights Into Olive Fruit Surface Functions: A Comparison of Cuticular Composition, Water Permeability, and Surface Topography in Nine Cultivars During Maturation - Diarte, Clara; Lai, Po-Han; Huang, Hua; Romero, Agustí; Casero, Tomás; Gatius, Ferran; Graell, Jordi; Medina, Vicente; East, Andrew; Riederer, Markus; Lara, Isabel (Frontiers in Plant Science, 2019)
Olive (Olea europaea L.) growing has outstanding economic relevance in Spain, the main olive oil producer and exporter in the world. Fruit skin properties are very relevant for fruit and oil quality, water loss and susceptibility to mechanical damage, rots and infestations, but limited research focus has been placed on the cuticle of intact olive fruit. In this work, fruit samples from nine olive cultivars (‘Arbequina’, ‘Argudell’, ‘Empeltre’, ‘Farga’, ‘Manzanilla’, ‘Marfil’, ‘Morrut’, ‘Picual’ and ‘Sevillenca’) were harvested from an experimental orchard at three different ripening stages (green, turning and ripe), and cuticular membranes were isolated enzymatically from fruit skin. The total contents of cuticular wax and cutin differed significantly among cultivars both in absolute and in relative terms. The wax to cutin ratio generally decreased along fruit maturation, with the exception of ‘Marfil’ and ‘Picual’. In contrast, increased water permeance values in ripe fruit were observed uniquely for ‘Argudell’, ‘Morrut’ and ‘Marfil’ fruit. The toluidine blue test revealed surface discontinuities on green samples of ‘Argudell’, ‘Empeltre’, ‘Manzanilla’, ‘Marfil’ and ‘Sevillenca’ fruit, but not on ‘Arbequina’, ‘Farga’, ‘Morrut’ or ‘Picual’. No apparent relationship was found between water permeability and total wax coverage or the results of the toluidine blue test. The composition of cuticular waxes and cutin monomers was analysed in detail, and sections of fruit pericarp were stained in Sudan IV for microscopy observations. Skin surface topography was also studied by means of fringe projection, showing large differences in surface roughness among the cultivars, ‘Farga’ and ‘Morrut’ fruit displaying the most irregular surfaces. Cultivar-related differences in cuticle and surface features of fruit are presented and discussed.